Peripheral Artery Disease in Vulnerable Patient Populations: Outcomes of Orbital Atherectomy in Native Americans Compared to Non-Native Americans. A Single-Center Experience in Rural Oklahoma - Ivan, Eugen; Martinsen, Brad; Igyarto, Zsuzsanna; Sublett, Tonya; Nachimuthu, Senthil (Cardiovascular revascularization medicine, 2021)
Although the incidence of peripheral artery disease (PAD) and amputations is higher in Native Americans (NA) than Caucasians, the study of revascularization NA is limited, resulting in their under representation in clinical studies. Orbital atherectomy (OA) is widely utilized for endovascular revascularization of significantly calcified peripheral arteries and has been shown to improve limb salvage rates. A cohort of 74 consecutive PAD subjects undergoing OA treatment was retrospectively analyzed via Kaplan Meier (KM) and Propensity Score Matched (PSM) analysis. A significant proportion of the subjects were NA (16.2%). Compared to the non-NA, the NA had higher numerical baseline rates of wounds, dialysis, chronic kidney disease (CKD), and critical limb ischemia, but were numerically less likely to smoke and had similar rates of diabetes. There were very high rates of severe calcification (100% vs. 87%) and pre-procedure diameter stenosis (99% vs. 95%) in both groups. The NA and non-NA had good angiographic outcomes, resulting in low rates of post-procedure residual diameter stenosis (10% vs. 11%). Lastly, KM analysis indicated high freedom from amputation in both groups at 1 year (89% vs. 95%), as well as in the PSM subjects (89% vs. 100%). Despite numerically higher rates of co-morbidities at baseline (e.g., CKD, dialysis, and presence of non-healing wounds), the NA underwent successful revascularization with OA, resulting in high freedom from amputation at 1-year. Given the small sample size of NA, these results may not be generalizable—thus, larger studies on NA are warranted. •The incidence of PAD and amputations is higher in Native Americans than Caucasians.•Native Americans (NA) are underrepresented in clinical trials.•The first orbital atherectomy (OA) study of NA with PAD•Treatment of NA with OA resulted in high freedom from major amputation at 1-year.